Transforming Leader Paradigms How to Replace Blanket Solutions with Problem Solving for Complexity. - Luckman, Jim.; Flory, Olga. (Milton : Productivity Press, 2019)
An easy read with clear examples and engaging stories, this book is a treat for leaders who are interested in totally transforming the way they work. Luckman and Flory help leaders and organizations shift from a solutions mindset to a problem-solving culture that results in flow and growth where everyone in the organization can become a winner. Anand V. Tanikella, Vice President R&D, Abrasives Worldwide, Saint-Gobain Luckman and Flory explain how to create a platform for change and a culture of meaningful continuous improvement through what they call "Problem Solving for Complexity." This approach is about engaging everybody in the organization to improve every aspect of how work gets done. Read this book if you want to be a real change leader, not just the person who goes around talking about the need for change. Robert Kessiakoff, Coach/Consultant, Partner LTGe, Sweden [This book] describes how the leader, through changing his or her own behaviors and practices, can transform an organization that is slow to adapt into one that solves problems organically. The book is an important read for leaders and managers at all levels. Peter Ward, Senior Associate Dean for Academics, Richard M. Ross Chair in Management, Professor of Management Sciences, Director, Center for Operational Excellence, Ohio State University Organizational transformation is difficult, and despite expensive continuous improvement programs, most change efforts fail. This pattern, James E. Luckman and Olga Flory argue, is due to the fact that most change efforts start with senior leaders assigning an external or internal consulting group to attempt to drive change from the top down. Leaders today can no longer roll out solutions in the hopes of seeing better results. What they can do is play an active role in helping to transform their organization from "blanket solutions" thinking to learning how to solve complex business problems in a rapidly changing world. Drawing upon decades of leadership experience and years of research with executives across many different industries, Luckman and Flory make a persuasive case that most companies have not been able to stay ahead in what is an increasingly turbulent business environment because they simply have not made the cultural changes required to do so. In discussing how to facilitate this culture change, the authors share a model for leadership designed to guide an organization to extraordinary new levels of performance by focusing on three key areas: building a framework for problem-solving, encouraging respectful communication, and accelerating the pace at which the organization learns. The result is more energized team members who are dedicated to their daily work in an organization that is better positioned to achieve operational excellence. Readers will also find powerful stories from executives who have effectively changed their approach to leadership, all of which serve to inspire more leaders to take the leap and become "problem-solvers for complexity." Transforming Leader Paradigms is a book about strengthening every organization's capacity to solve complex business problems. But, more importantly, it's about what leaders must change in themselves to help their team members solve problems methodically, start to look at the world differently using complexity theory, and understand what it means to create real value for customers. For leaders who are willing to examine their own behaviors, this book is a welcome change from the steady stream of business books on the market that emphasize charismatic and/or heroic leadership as the key to achievement and success.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Management; Leadership; Problem solving